(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
This scientific article presents a comprehensive study of audio signals’ fundamental frequency detection methods, focusing on both time-domain and frequency-based approaches and audio file processing since it is crucial for the post-processing part of the audio plug-ins for which this study is intended. Additionally, the article introduces self-repairing algorithms that adaptively identify and correct errors in the detected signals, ensuring robustness and accuracy in signal processing tasks and enhancing the overall detection performance. The findings from this study offer valuable insights into advancing signal processing techniques with broader implications across various domains.